HUBUNGAN POWER OTOT LENGAN DENGAN FREKUENSI PUKULAN LURUS PADA OLAHRAGA PENCAK SILAT MAHASISWA ILMU KEOLAHRAGAAN ANGKATAN 2017 FKIP UHO - Fildayanti Fildayanti; Wolter Mogsidi; Muh. Rusli (universitas halu oleo, 2020)
This research included korelasional's research that wants to know how big relationship power arm muscle with straight smitten frequency on olaraga pencak silat keolarahragaan's knowledge college student generation 2017 FKIP UHO. Population in observational it is exhaustive keolahragaan's knowledge college student generation 2017 FKIP UHO already follow pencak silat's lecturings to amount to 65 person, one that consisting of 56 sons and 9 daughters, and sample take tech with tech purposive random is sampling namely take sample with consideration gets son gender 56 Person then done by random random / simples so is gotten 35 person that is plotted as sample of research. Meanwhile instrument which is utilized is essay power arm muscle by essays to throw ball gets charges (medicine ball), essay straight smitten frequency to measure frequency amount that can do college student up to 30 seconds. analisis's tech data that is utilized is with tech statistic correlation product momen with signifikan's level 0,05. This observational result menunjukan that there is relationship which wherewith among power arm muscle with lururs's smitten frequency, Where (r xy ) = 0,70> r table (0,005:35) = 0,334 by determinant coefficient 0,49 or 49%. Of acquired result gets disimpulakan that exists relationship that bermakana among power arm muscle with straight smitten frequency on pencak silat's sport keolaharagaan's knowledge college student generation 2017 FKIP UHO.